KEBIJAKAN HUKUM PIDANA DAN IMPLEMENTASINYA DALAM UPAYA MEMBERIKAN PERLINDUNGAN TERHADAP ANAK DARI TINDAK KEKERASAN (Studi Kasus Pada Pengadilan Negeri Kelas I A Palu) - Achmad Allang; H. Amiruddin Hanafi; Andi Nurul Isnawidiawinarti Achmad (Fakultas Hukum Universitas Muhammadiyah Palu, 2019)
The Child Protection Act has undergone two changes, but acts of violence against children continue to occur, and even tend to increase, including in the city of Palu. The problem of this research is how the criminal law policy in providing legal protection to children from violence and its implementation in the territory of the Class I A District Court hammer. This study aims to determine the criminal law policy and its implementation provides legal protection against children from acts of violence in the jurisdiction of Class I A Palu District Court. The research method used is a normative legal research method that focuses on the study of legislation relating to child protection and official documents contained in the Police, Attorney General's Office, and the Women's Empowerment Office and analyzed descriptively. Research results show that substantively (normative) criminal law policy is sufficient to provide legal protection from violence, but its implementation does not yet reflect justice to victims and law enforcers have not optimally applied the laws and regulations relating to child protection. Keyword: criminal law policy, implementation of child protection, violence against children